2010
DOI: 10.1128/cvi.00529-09
|View full text |Cite
|
Sign up to set email alerts
|

Updated Postlicensure Surveillance of the Meningococcal C Conjugate Vaccine in England and Wales: Effectiveness, Validation of Serological Correlates of Protection, and Modeling Predictions of the Duration of Herd Immunity

Abstract: Meningococcal serogroup C conjugate (MCC) vaccines were licensed in the United Kingdom more than 10 years ago based on correlates of protection that had previously been established for serogroup C-containing polysaccharide vaccines by using the serum bactericidal antibody (SBA) assay. These correlates of protection were subsequently validated against postlicensure estimates of observed vaccine effectiveness up to 7 to 9 months after the administration of the MCC vaccine. Vaccine effectiveness was, however, sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
133
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(146 citation statements)
references
References 38 publications
5
133
1
7
Order By: Relevance
“…1 Modelling studies in England suggest that carriage reduction achieved by the catch-up campaign, particularly in adolescents, who have the highest carriage rates 19 and 20 remains instrumental in maintaining low IMD incidence in the UK. 21 This is supported by data reported to ECDC, 1 according to which the proportion of SgC IMD among all serogrouped IMD cases in 2009 was 0% in Iceland, 0.5% in the UK, 5.1% in the Netherlands, 3.7% in Ireland, and 1.8% in Portugal, where catch-up campaigns targeted all persons up to 18 years or even older. In contrast, in Spain, where catch-up vaccination was limited to children 5 years and younger in 16/19 regions 22 and Belgium, 23 where catch up was limited to 1-6 year-olds in French regions and to 1-6 year olds and 15-18 year-olds in Flanders, the proportion of SgC IMD was higher at 7.1% and 13.8%, respectively, but still lower than in Germany (21.9%) or in countries that did not implement SgC vaccination before 2010, e.g.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…1 Modelling studies in England suggest that carriage reduction achieved by the catch-up campaign, particularly in adolescents, who have the highest carriage rates 19 and 20 remains instrumental in maintaining low IMD incidence in the UK. 21 This is supported by data reported to ECDC, 1 according to which the proportion of SgC IMD among all serogrouped IMD cases in 2009 was 0% in Iceland, 0.5% in the UK, 5.1% in the Netherlands, 3.7% in Ireland, and 1.8% in Portugal, where catch-up campaigns targeted all persons up to 18 years or even older. In contrast, in Spain, where catch-up vaccination was limited to children 5 years and younger in 16/19 regions 22 and Belgium, 23 where catch up was limited to 1-6 year-olds in French regions and to 1-6 year olds and 15-18 year-olds in Flanders, the proportion of SgC IMD was higher at 7.1% and 13.8%, respectively, but still lower than in Germany (21.9%) or in countries that did not implement SgC vaccination before 2010, e.g.…”
Section: Discussionmentioning
confidence: 56%
“…In this survey, vaccination coverage was highest in children aged 2-5 years (78.3%), followed by 6-10 year olds (58.6%), 0-1 year olds (36.3%), 11-16 year olds (36%), and 17-18 year olds (27.8%)(F. Weidle, GfK, personal communication). These rates are much lower than those achieved in countries such as the UK (≥93% by second birthday since 2005, and ≥85% among 5-17 year old children in the schoolbased catch-up campaign 21 ) or the Netherlands, in which coverage of 94% was achieved in 1-18 year old persons within the catch-up campaign. 17 Thus, vaccination coverage attained through a recommendation for "individual"-based catch-up in Germany appears inadequate to achieve reduction of carriage in older children with the highest carriage rates, 24 and thus to have a major impact on transmission.…”
Section: Discussionmentioning
confidence: 64%
“…9 In this light, catch up programs could be strengthened because it is well known that the impact of vaccine is also linked to its efficacy against carriage in older age groups and therefore to herd immunity. [27][28][29][30] As far as the other serogroups are concerned, our study showed that the incidence of serogroup B related IMD remained stable in the pre and post vaccination era even though the relative proportion of cases due to N. meningitidis B has increased over time. The incidence of IMD due to serogroups A, W135, X, Y has increased during 2005-2012.…”
Section: Discussionmentioning
confidence: 86%
“…To establish a population correlate of protection, the titre obtained by majority of vaccinated group is compared to titre obtained by majority of unvaccinated group can be compared with the vaccine efficacy in a specific age group. Campbell et al reported 6 an SBA titre of 8 was found to give a strong correlation with vaccine efficacy and led to the establishment of an SBA titre of 8 as a population based correlate. Hence, data are compared in this review using both the percentage of subjects with SBA titres 8 and the SBA GMTs.…”
Section: Three Dose Infant Schedulementioning
confidence: 99%
“…5 A 3 dose course in infancy has been shown to provide high short term protection, with vaccine effectiveness at 97% within a year of vaccination which significantly falls to 68% more than a year after vaccination. 6 The pre-implementation trial of Richmond et al (1999) showed there to be little difference between 2 and 3 doses of MCC in UK infants, with, the serum bactericidal antibody (SBA) geometric mean titres (GMTs) one month following 2 doses administered at 2 and 3 months of age to be 766.3 (95%CI 500-1174) compared to 1001 (95%CI 702-1455) one month following a third dose at 4 months of age. At both time points, 98% of subjects achieved an SBA titre of 8, the titer considered to be protective.…”
Section: Three Dose Infant Schedulementioning
confidence: 99%